Studi Toksisitas: Ekstrak Metanol Bonggol Pisang Ambon (Musa acuminata L. cv. Gros Michel) terhadap Aedes aegypti (Diptera: Culcidae) - Siskha Noor komala; Bambang Heru Budianto; Edi Basuki (ASPIRATOR - Journal of Vector-borne Disease Studies, 2018)
Aedes aegypti mosquito is the main vector of dengue virus causing dengue hemorrhagic fever (DHF) in Indonesia. The main preventive action is to control the presence of Ae. aegypti mosquito. Banana plants are known to contain secondary metabolite compounds acting as a natural insecticide, including the hump part. This research was conducted to evaluate to toxicity of hump of Ambon banana extract (Musa acuminata L. cv. Gros Michel) to dengue vector Ae. aegypti mosquito. The research used experimental method, the treatment concentration was 0.001; 0.01; 0.1; 1; 10; 100 and 1000 ppm of Ambon banana methanol extract and 0 ppm concentration as a control, each with three replications. The variables observed were individual deaths at every stage of development and morphological damage. The data obtained were analyzed using the analysis of variety and Duncan test with 95% confidence level. In addition, probit analysis was used to determine the value of LC50. The results showed that the study of toxicity indicates that in the further stage of development, the toxicity of methanol extract from Ambon banana hump was less toxic. Toxicity of Ambon banana hump methanol extract was highest in egg with LC50 value of 314,852 ppm. The methanol extract of banana Ambon has the morphological destructive activity in all development stages of Ae. aegypti.